SOCIO-EMOTIONAL COMPETENCE AND PERSONALITY TRAITS AS DETERMINANTS OF JOB PERFORMANCE AMONG SECONDARY SCHOOL TEACHERS IN ABIA STATE (Journal of Guidance and Counselling Studies, 2022)
This study examined the influence of socio-emotional competence and Personality traits as determinant of job performance among secondary school teachers in Abia State. Correlational study was adopted. Two research questions and two corresponding null hypotheses were stated. A sample of 878 teachers was drawn using proportionate stratified random sampling. Three self-developed instruments were made through extensive review of literature namely: Personality Traits Assessment Questionnaire (PTAQ), Socio-emotional Competence Questionnaire (SECQ)andJob Performance Questionnaire (JPQ) and used for data collection. The data generated for this study were analyzed using Pearson Product Moment Correlation Analysis (PPMC). The extent or strength of relationship of the variables was interpreted using Creswell (2008) correlation coefficient scale. Scheffe test was also done for a step-wise comparison of the means research questions/hypotheses one and two to determine the direction of the relationship. The following were some of the findings: Teachers’ social skills to a high positive extent determine their job performance. Self-management to a moderate positive extent determines job performance among secondary school teachers in Abia State. Based on the findings of the study, it was recommended that teachers should endeavour to manifest only the personality traits that relate positively with teaching and job effectiveness so as to produce effective students. Employers of labour should consider only teachers who have good personality traits and socio-emotional competence variables necessary for effective teaching and learning to ensure improved productivity in our schools.